Risk Factors of Hypertension in High School Students: Multilevel Evidence of The Contextual Effect of School - Mayasari Kurnianingsih; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2019)
Background: In 2025, it is projected that 29% of the world's citizens will suffer from hyper